Phylogenomic analysis, cryptic species discovery, and DNA barcoding of the genus Cibotium in China based on plastome data - Jiang, Ri-Hong; Liang, Si-Qi; Wu, Fei; Tang, Li-Ming; Qin, Bo; Chen, Ying-Ying; Huang, Yao-Heng; Li, Kai-Xiang; Zhang, Xian-Chun (Frontiers in Plant Science, 2023)
Germplasm resources are the source of herbal medicine production. Cultivation of superior germplasm resources helps to resolve the conflict between long-term population persistence and growing market demand by producing materials with high quality consistently. The fern species Cibotium barometz is the original plant of cibotii rhizoma (“Gouji”), a traditional Chinese medicine used in the therapy of pain, weakness, and numbness of lower extremities. Long-history medicinal use has rendered wild populations declined seriously in China. Without sufficient understanding of species and lineage diversity of Cibotium, it is difficult to propose a targeted conservation scheme at present, let alone selecting high-quality germplasm resources. In order to fill such a knowledge gap, this study sampled C. barometz and relative species throughout their distribution in China, performed genome skimming to obtain plastome data, and conducted phylogenomic analyses. We constructed a well-supported plastome phylogeny of Chinese Cibotium, which showed that three species with significant genetic difference distributed in China, namely C. barometz, C. cumingii, and C. sino-burmaense sp. nov., a cryptic species endemic to NW Yunnan and adjacent region of NE Myanmar. Moreover, our results revealed two differentiated lineages of C. barometz distributed in the east and west side of a classic phylogeographic boundary that probably shaped by monsoons and landforms. We also evaluated the resolution of nine traditional barcode loci, and designed five new DNA barcodes based on the plastome sequence which can distinguish all these species and lineages of Chinese Cibotium accurately. These novel findings integrated genetic basis will guide conservation planners and medicinal plant breeders to build systematic conservation plans and exploit germplasm resources of Cibotium in China.